Luck and leaps of faith: how the digital informal economy transforms the geographies of shared renting in Australia. (22nd November 2021) - Parkinson, Sharon; James, Amity; Liu, Edgar
ABSTRACT: Shared rental housing has long been one of the few affordable options available to low-income urban singles. Gaining access to a share rental dwelling has historically relied on 'low tech' communications such as noticeboards and classifieds, in relatively localised spatial areas. With the global proliferation of digitally mediated peer-to-peer platforms, the geographical reach of shared renting, including the opportunity for living with strangers, has expanded. Amidst declining affordability and growing precarity, the enhanced spatial flows and connectivity of peer-to-peer platforms provide a direct yet informal route into rental housing. In these informal spaces, singles rely on networks of 'distributed' rather than 'institutional' trust associated with formal rental arrangements. Drawing on interviews with urban singles in Australia, this paper explores the everyday informal practices of forming networks for shared access, negotiating the living agreement, creating a home and becoming an expert in the digitally mediated spaces of the shared rental household. The everyday informal practices of 'distributed trust' sheds new light on the spatially contingent 'trust cultures' emerging in shared renting. Despite narratives of a movement towards the more collaborative consumption of a sharing economy, enduring informal practices of opportunists and entrepreneurs that erode trust and a sense of home persist.